KEPEMILIKAN MANAJERIAL DAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, STRUKTUR AKTIVA DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG - Yuli Soesetio (Jurnal Keuangan dan Perbankan, 2008)
This research was conducted to know several factors that affected Debt policy andto know the significance level and the correlation between dependent and independent variable.Analysis instrument used was parametric statistic. Based on the result of statistic test, all ofindependent variables were able to explain simultaneously dependent variable of Debt policy,and particularly, variable of Managerial Ownership, Institutional Ownership, Assets Structure,and Profitability which were affected significantly towards Debt policy.